Credit rating and stock return comovement - Shen, Jianfeng; Zhang, Huiping; Zhang, Weiqi (Journal of Banking & Finance, 2025)
Firms with similar credit ratings, particularly high-yield ones, exhibit strong comovement in stock returns . After a firm is downgraded to high-yield status, it comoves more with other high-yield firms and less with investment-grade ones, a pattern not fully explained by changes in fundamentals or other firm characteristics. We find evidence that suggests the investor clientele explanation for rating-related comovement, potentially arising from heterogeneous lottery preferences. High-yield-averse funds reduce their holdings of firms being downgraded to high-yield status, particularly those that are more lottery-like, much more significantly than high-yield-prone funds. Furthermore, a firm’s stock returns become sensitive to flows into high-yield-prone funds after being downgraded to high-yield status, consistent with the price impact of rating-based category investing.